An approach of territorial arrangement of Cali – Colombia - Vergara Varela, Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This working paper describes, analyzes and evaluates public policy of urban development of the Land Use Plan (POT, 2000) in the city of Cali. The incidence of such public policy within the physical transformation of the city can be showed through as elementary as it is the price of urban land indicator -in relation to the market price of urban land because this factor market signaler determines the rules of the game in a society-. I.e., we have a methodological tool in terms of evaluation of these specific public policies.